2012
DOI: 10.1097/gme.0b013e3182503834
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics and obesity in middle-aged women seen at an outpatient clinic in southern Brazil

Abstract: Characteristics of reproductive life may have a strong influence on body fat buildup in women during the menopausal transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
2
16
0
5
Order By: Relevance
“…In addition, the prevalence rates of excess weight (69.2%) and abdominal obesity (62.3%) were shown to be high among women studied in 2015 who exhibited this characteristic, corroborating the studies by Pinheiro et al [40] and Trikudanathan et al [41]. A study conducted in the South of Brazil showed that women who had their menarche before age 11 had a 25% higher risk of having abdominal obesity and a 75% higher risk of being obese [42]. In the semiarid region of Brazil, this risk was increased by 59% [14].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the prevalence rates of excess weight (69.2%) and abdominal obesity (62.3%) were shown to be high among women studied in 2015 who exhibited this characteristic, corroborating the studies by Pinheiro et al [40] and Trikudanathan et al [41]. A study conducted in the South of Brazil showed that women who had their menarche before age 11 had a 25% higher risk of having abdominal obesity and a 75% higher risk of being obese [42]. In the semiarid region of Brazil, this risk was increased by 59% [14].…”
Section: Discussionsupporting
confidence: 80%
“…Early menarche, before the age of 12, has been associated with a higher prevalence of AO [30][31][32][33]. Both early menarche and early menopause can be considered as increased risk factors for cardiovascular disease.…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 99%
“…For example, a cross-sectional study with a sample of 617 women from southern Brazil observed that women with a history of three or more pregnancies and menarche at the age of 11 or earlier had a 25% higher prevalence of AO compared to nulliparous or primiparous women with menarche at 14 years or older [31]. Studies show that the number of parturitions leads to a tendency of decreased hip circumference and increased WC [37][38][39].…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Entre as reações fisiológicas provocadas pelo excesso de peso, estão a sintetização da angiotensina II pelo tecido adiposo e alojamento em sua membrana da subunidade AT1 do receptor da angiotensina, com probabilidades de os componentes do sistema renina-angiotensina dos adipócitos compartilharem da fisiopatologia da hipertensão e doença cardiovascular. Além disso, o tecido adiposo sintetiza e secreta vários outros mediadores e citocinas próinflamatórias, que participam de mecanismos que induzem a dislipidemia, resistência à insulina, hipertensão arterial e aterosclerose (17) .…”
Section: Discussionunclassified